Ṭabaqāt al-Mufassirīn by al-Suyūṭī and the Affirmation of Non-Sunni Mufassir Authority: A Historiographical Analysis - Nastiar, Muhammad Addien; Miski, Miski (Institut Agama Islam Negeri (IAIN) Keiri, 2023)
Al-Suyūṭī's Ṭabaqāt al-Mufassirīn is the first work of tafsir historiography that became the beginning of the ṭabaqāt genre in the field of exegesis. With regard to the explanation of the exegetes' profiles, there is an interesting fact that al-Suyūṭī (d. 911 AH/1505 CE), who is known as a Sunni scholar, also included the names of non-Sunnī mufasirs (Mu'tazilah and Shī'ah). There are at least eight Mu'tazilah and three Shī'ah mufasirs. A number of important non-Sunnī figures he wrote about such as al-Jubbā'Ī, al-Zamakhsharī, Abū Yusūf Al-Qazwīnī, and others. Based on this fact, a question arises, how does al-Suyūṭī present and construct the authority of non-Sunnī mufasirs in the work? However, this question becomes important because al-Suyūṭī himself was of Sunnī ideology and became a Sunnī figure and automatically played a role in the contestation between ideologies at that time. Using a historiographical approach and interpretative analysis, this study shows that al-Suyūṭī's presentation of non-Sunnī figures appears empathetic by not differentiating patterns in describing the profiles of Sunnī and non-Sunnī figures. The construction of non-Sunnī authority is presented by emphasising the expertise of the relevant figures, the works produced, and positive testimonials in other experts related to the field of the Qur'an. This implies how an attitude of fairness, moderation, tolerance, and respect for differences has been shown by Al-Suyūṭī.